Aircraft observations and model simulations of the Asian summer monsoon outflow during ESMVal - Gottschaldt, Klaus-Dirk; Schlager, Hans; Eyring, Veronika; Hoor, Peter; Jöckel, Patrick; Jurkat, Tina; Voigt, Christiane; Ziereis, Helmut (2015)
The main objective of the ESMVal field experiment using the HALO research aircraft was to sample observational data for the evaluation of Earth system models, in particular the ECHAM/MESSy Atmospheric Chemistry (EMAC) model. The HALO mission included pole to pole survey observations of trace gas distributions in the UTLS from Spitsbergen in the Arctic to the boundary of the Antarctic continent, and detailed profile measurements for sampling of air masses impacted by specific dynamical and chemical processes. During a flight on 18 Sept. 2012 from the Maledives to Cyprus the outflow of the Asian summer monsoon anticyclone in the upper troposphere was successfully sampled. The origin of the air masses probed is polluted boundary layer air from northern India and the Gulf of Bengal, convectively uplifted to the measurement altitudes. In addition, these air masses partly mixed with air of stratospheric origin in the monsoon anticyclone. We present the HALO observations and accompanying EMAC simulations.